The impact of the Canterbury earthquakes on dispensing for older person's mental health. (7th August 2019) - Beaglehole, Ben; Bloomer, Christopher; Zhang, Tao; Hamilton, Greg; Boden, Joseph M.; Mulder, Roger T.; Bell, Caroline; Frampton, Chris
Abstract : Objective: To evaluate the impact of the Canterbury earthquakes on the mental health of older people by examining dispensing patterns of psychotropic medication. Method: Dispensing data from community pharmacies for antidepressants, antipsychotics, anxiolytics, and sedative/hypnotics are routinely recorded in a national database. Longitudinal data are available for residents of the Canterbury District Health Board (DHB) (n = 67 760 at study onset) and the rest of New Zealand (n = 469 055 at study onset). We compared older age dispensing data between 2008 and 2018 for Canterbury DHB with older age dispensing data nationally in order to assess the impact of the Canterbury earthquakes on the mental health of older persons. Results: Older age residents of Canterbury are dispensed antidepressants, antipsychotics, and anxiolytics at higher rates than national comparators, but this finding predated the onset of the earthquakes. Short‐term increases in anxiolytic and sedative/hypnotic dispensing occurred for the month following the February 2011 earthquake. No other short‐ or longer‐term increases in dispensing of psychiatric medication were present. Conclusion: The February 2011 Canterbury earthquake caused a short‐term increase in dispensing of anxiolytics and sedative/hypnotics. No longer‐term effects on dispensing were observed. This suggests that older persons sought assistance for insomnia and anxiety in the aftermath of the most devastating earthquake, but longer‐term rates of clinically significant anxiety and depression for older persons did not increase as a consequence of the earthquakes sequence